Harnessing fungal endophytes for natural management: a biocontrol perspective - Bhardwaj, Mansavi; Kailoo, Swadha; Khan, Rabiya Tabbassum; Khan, Sofia Sharief; Rasool, Shafaq (Frontiers in Microbiology, 2023)
In the ever-evolving realm of agriculture, the convoluted interaction between plants and microorganisms have assumed paramount significance. Fungal endophytes, once perceived as mere bystanders within plant tissues, have now emerged as dynamic defenders of plant health. This comprehensive review delves into the captivating world of fungal endophytes and their multifaceted biocontrol mechanisms.Exploring their unique ability to coexist with their plant hosts, fungal endophytes have unlocked a treasure trove of biological weaponry to fend off pathogens and enhance plant resilience. From the synthesis of bioactive secondary metabolites to intricate signaling pathways these silent allies are masters of biological warfare. The world of fungal endophytes is quite fascinating as they engage in a delicate dance with the plant immune system, orchestrating a symphony of defense that challenges traditional notions of plant-pathogen interactions. The journey through the various mechanisms employed by these enigmatic endophytes to combat diseases, will lead to revelational understanding of sustainable agriculture.The review delves into cutting-edge research and promising prospects, shedding light on how fungal endophytes hold the key to biocontrol and the reduction of chemical inputs in agriculture. Their ecological significance, potential for bioprospecting and avenues for future research are also explored. This exploration of the biocontrol mechanisms of fungal endophytes promise not only to enrich our comprehension of plantmicrobe relationships but also, to shape the future of sustainable and ecofriendly agricultural practices. In this intricate web of life, fungal endophytes are indeed the unsung heroes, silently guarding our crops and illuminating a path towards a greener, healthier tomorrow.